2005
DOI: 10.1074/jbc.m410361200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Essential Interactions Involved in the Assembly of Hepatitis E Virus Capsid

Abstract: The hepatitis E virus (HEV) capsid consists of a single structural protein, a portion of which is engaged in isosahedral contact to form a basal shell, and another portion in dimeric contact to form the homodimers protruding from the shell. Previous studies revealed that homodimers of the truncated HEV capsid proteins, E2 (amino acids 394 -606) and p239 (amino acids 368 -606), model dominant antigenic determinants of HEV. Immunization with these proteins protected rhesus monkeys against the virus, and three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 22 publications
3
74
0
4
Order By: Relevance
“…Cloning, Expression, and Purification of p239 and Mutant Antigens-The gene encoding p239 was described previously (36). Genes for mutant antigens with the surface amino acids replaced by alanine (Ala) were prepared by site-directed mutagenesis using polymerase chain reaction (PCR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning, Expression, and Purification of p239 and Mutant Antigens-The gene encoding p239 was described previously (36). Genes for mutant antigens with the surface amino acids replaced by alanine (Ala) were prepared by site-directed mutagenesis using polymerase chain reaction (PCR).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the outer membrane protrusions on other viral surfaces (26 -30), the HEV E2s domain harbors the major neutralizing epitopes for protection (31)(32)(33)(34)(35). A series of recombinant proteins containing the E2s domain, which included the bacterially expressed truncated proteins pE2 (aa 394 -606) (22,23,36) and p239 (aa 368 -606) (37) and the baculovirus expression system expressed T ϭ 1 virus-like particle (21), protected non-human primates and humans efficiently against HEV infection and liver injury (32,34). Among the truncated proteins, p239 was successfully used in the only approved HEV vaccine (32).…”
Section: Hepatitis E Virus (Hev)mentioning
confidence: 99%
“…The E2s, E2 and p239 genes of HEV were cloned as previously described [12,17]. All mutated constructs were generated with site-directed PCR reactions.…”
Section: Construction and Antibody Preparationmentioning
confidence: 99%
“…We have previously shown that a truncated form of this capsid protein, p239 (aa 368-606) can self-assemble into virus-like particles (VLPs) of ~23 nm in diameter and subsequently penetrate susceptible cells, similar to a live virus [12]. We later produced the recombinant vaccine, HEV239, and employed this in a randomized, double-blind, placebo-controlled, phase 3 clinical trial involving more than 100 000 volunteers [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation